Special features of the life of the Panar - S, Amutha (International Research Journal of Tamil, 2021)
The Sangam books of the Eight anthologies and Ten Idylls contain the books of the Aatrupadai. Sangam literature is considered to be classical literature in tamil language. The Sangam poets have embodied all their life experiences in the songs. The Sangam hymns are the literature that records the experiences of man. Though the life that man lives on earth is a very short life, the difficulties and difficulties that man faces in his life are numerous. In later years, the books of the Aatrupadai were given as chitrilakyams in Tamil and prabandhas in Sanskrit. Thus they made it one of the types of songs. Counseling means guiding. Poets used to go to the philanthropists to sing songs and get prizes to alleviate their poverty. There are four kinds of groups viz., Viraliyar, Panar, Kootha and Porunar. Within these four categories, the Aatrupadai consists in the way in which one person leads the other to receive a gift. External song which is composed of hymns, speaks of the leader's fame, gifts and heroism. If the internalism describes the life of the leader and the leader, the exegesis conveys a community by telling the history of the king. Thus, the life of the Banas is shaped by the songs of the Panar.